A Media Biopsy: Examining the Quality of Cancer Reporting in Australia, 1997 and 2017. Issue 10 (24th August 2021) - Lawler, Nicholas; Carson, Andrea; Gravelle, Tim; Brett, Andrew
ABSTRACT: This article investigates the quality of cancer reporting from a time of prosperity to a time of austerity for the press. Australia is a useful case study because of its concentrated press media market that has experienced a decline in the number of newsroom reporters from the 20 th to the 21 st century. We undertake a content analysis of news stories published in 1997 and 2017 about cancer treatments and cancer medical research. Using keyword searching techniques of the news database Factiva, 633 news reports about cancer were detected. Of these, 120 stories met the research criteria. Each story was assessed across eight variables using a coding tool, the Media Quality Index (MQI). The study finds 2017 stories had lower scores (equating to less quality) across all eight variables compared to the 1997 cohort. Of statistical significance, 2017 stories were less likely to quantify the benefits of a proposed intervention, while stories discussing medical research were less comprehensive about research findings. The 2017 stories were less likely to discuss side effects or the potential for harm, and were more sensational, with incongruent headlines compared to content. The empirical evidence pointing to a deterioration in mainstream media reporting about cancer has implications for broader health literacy. It may foster unrealistic patient expectations about clinical practice and treatment options, with public policy implications such as overutilization of health services. The study serves as a reminder to medical practitioners that health communication directly with patients is vital as media reporting alone cannot reliably inform patients about their cancer diagnosis and treatment.